Odpowiedź :
Odpowiedź:
6x+3=33
6x=33-3
6x=30/:6
x=5
3-10x=9-4x
-10x+4x=9-3
-6x=6/:(-6)
x= -1
4x+8+2x=6x+8
4x+2x-6x=8-8
0=0
2x+8=2(x+3)
2x+8= 2x+ 6
2x-2x=6-8
0= -2
Odpowiedź:
a) 6x + 3 = 33. |-3
6x= 30 |:6
x= 5
Sprawdzenie
6*5+3=30+3= 33
33=33
b) 3 - 10x = 9 – 4x |+10x
3=9+6x |-9
-6= 6x |:6
x= -1
Sprawdzenie
3- 10*(-1)= 3-(-10)= 13
9-4*(-1)= 9-(-4)= 9+4=13. 13=13
c) 4x + 8 + 2x = 6x + 8 |
6x+8=6x+8 |-8
6x=6x |:6
x=x
Każda liczba jest rozwiązaniem
Sprawdzenie
np. 3
4*3+8+2*3= 6*3+8
12+8+6= 18+8
26=26
np. -5
4*(-5)+8+2*(-5)= 6*(-5)+8
-20+8-10= -30+8
-22= -22
d) 2x + 8 = 2(x + 3)
2x+8= 2x+6 |-6
2x+2=2x |-2x
2= 0
ŻADNA LICZBA NIE SPEŁNIA RÓWNANIA